On the Problems of Application of Institute of Cancellation of the Documentation on a Lay-out of Territory, Recognition of Separate Parts of Such Documentation not Subject to Application - A. V. Basharin (Теоретическая и прикладная юриспруденция)
In article problems at application rather new institute of the town-planning legislation cancellation of the documentation on a lay out of territory, recognition of separate parts of such documentation not subject to application are considered. The author tries to reveal distinctions between cancellation of such documentation and recognition of separate parts not subject to application, considers a number of questions connected with possibility of cancellation of the documentation on a territory planning corresponding to legislative requirements. Also the attention is given to definition of the subject structure of the persons empowered on cancellation of the documentation on a lay-out of territory, necessity of carrying out of public hearings in the course of such cancellation. In conclusion, the author draws the main conclusions, once again drawing attention to the existence of systemic shortcomings of the existing public law regulation.